Industrial Practice and Communication Skills: Work Readiness of Electronic Engineering Education Students - Vionisa Gassa Langan; Hasanah Nur; Muh. Ma'ruf Idris (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
This study examines the effect of industrial practice and communication skills on the work readiness of students in the Electronic Engineering Education Department at Universitas Negeri Makassar, Indonesia. Work readiness is a crucial outcome of higher education, particularly for students preparing to enter the professional workforce, yet prior studies have rarely modeled industrial practice and communication skills jointly within a single regression framework in the vocational-engineering context. A quantitative ex-post facto design was employed, drawing on the entire population of 47 fourth-year students who had completed their industrial internship, using a validated four-point Likert-scale questionnaire (15 items per variable). Data was analyzed through multiple linear regression in IBM SPSS Statistics 29, following tests of validity, reliability, and classical assumptions. The results show that (1) industrial practice has a positive and significant partial effect on work readiness (t = 2.165, sig. = 0.034 < 0.05); (2) communication skills have a positive and significant partial effect on work readiness (t = 3.580, sig. = 0.001 < 0.05); and (3) industrial practice and communication skills simultaneously and significantly affect work readiness (F = 86.529, sig. = 0.001 < 0.05), jointly explaining 78.8% of the variance in work readiness (Adjusted R² = 0.788), with communication skills exerting the more dominant influence (b = 0.709) relative to industrial practice (b = 0.240). These findings suggest that vocational teacher-education curricula should integrate structured industrial-practice programs with deliberate communication-skills training to strengthen graduate employability.